Techno cops [police robotic and electronic technology]. - Kumagai, J. (IEEE spectrum)
The LA. sherriff's deputy Sid Heal is creating a world-renowned test bed for police technology to combat criminals. This paper describes Heal's technology project which was started in 1997 with the emphasis on nonlethal weapons such as the taser. In 2001 the technology development project was opened up beyond nonlethal weapons to include anything useful to the bureau. He assigned a SWAT team to be his technical-assault squad. Though this squad still trains and operates just like the other SWAT teams, its members are also responsible for deploying robotics and electronics equipment as needed, and for scouting out and evaluating new products.